Molecular characterization and chromosomal localization of two families of satellite DNA in Prochilodus lineatus (Pisces, Prochilodontidae), a species with B chromosomes - De Jesus, Célia Maria; Galetti Jr., Pedro M.; Valentini, Sandro Roberto [UNESP]; Moreira-Filho, Orlando (Springer Nature, 2003)
Prochilodus lineatus, an abundant species in the Mogi-Guaçu river basin, represents a large part of the region's fishing potential. Karyotypic analyses based on classic cytogenetic techniques have revealed the presence of 54 metasubmetacentric type chromosomes, together with the occurrence of small supernumerary chromosomes with intra and interindividual variations. This paper describes the genomic organization of two families of satellite DNA in the P. lineatus genome. The chromosomal localization these two repetitive DNA families through fluorescence in situ hybridization (FISH) demonstrated that the SATH1 satellite DNA family, composed of approximately 900 bp, was located in the pericentromeric region of a group of chromosomes of the standard complement, as well as on all the B chromosomes. The SATH2 satellite family has a monomeric unit of 441 bp and was located in the pericentromeric regions of some chromosomes of the standard complement, but was absent in the B chromosomes. Double FISH analyses showed that these two families participate jointly in the pericentromeric organization of several chromosomes of this species. The data obtained in this study support the hypothesis that the B chromosomes derive from chromosomes of the standard complement, which are carriers of the SATH1 satellite DNA.
Keywords: B chromosome; FISH; Pisces; Prochilodus lineatus; Satellite DNA; Animals; Blotting, Southern; Brazil; Chromosome Mapping; DNA, Satellite; Fishes; In Situ Hybridization, Fluorescence; Sequence Alignment; Prochilodontidae